Controlled growth of SnO2 nanorods clusters via Zn doping and its influence on gas-sensing properties - Ding, Xiaohu; Zeng, Dawen; Xie, Changsheng (Sensors and actuators. B, Chemical, 2010)
Zn-doped SnO2 nanorods clusters with controllable size (the length and the diameter of nanorods) are prepared by adjusting the Zn2+ concentration in the precursor solution using a facile hydrothermal process. The as-synthesized samples are characterized by powder X-ray diffraction, scanning electron microscopy, transmission electron microscopy (TEM), high-resolution TEM, and energy-dispersive X-ray spectroscopy (EDS). With an increase of the molar ratio of Zn2+/Sn4+ in the solution, the length of the Zn-doped SnO2 nanorods gradually increases, and the average length of the nanorods reaches the maximum of 239nm at 0.133. However, when the molar ratio of Zn2+/Sn4+ is increased to 0.2, the length of the nanorods decreases accompanied with the generation of Zn2SnO4 phase. The Zn-doped SnO2 nanorods grow along the [112] direction and the possible growth mechanism is proposed. The gas-sensing properties of the obtained Zn-doped SnO2 samples are tested towards methanol gas. And, it is found the composition-morphology-performance relationship that the more the doping content of Zn, the longer the length of nanorods and the higher the response to methanol, which is significant for the preparation and the design of gas-sensing materials with the high performance.